The Tea Dragon Society - O'Neill, Katie (Cartoonist) (Oni Press, 2017)
After finding a lost Tea Dragon, Greta befriends tea shop owners Erik and Hesekiel--along with their ward Minette-- who teach her the waning art of caring for Tea Dragons, and in the process, she learns much about herself.